LDPC Coded Angular Modulation Scheme for Cooperative Wireless Networks; IEEE 84th Vehicular Technology Conference (VTC Fall) - Dzhayakodi Arachshiladzh D. N. K. Dushanta Nalin Kumara (2017, 2017)
Title screen